The book embedding of Schrijver graph - Shao, Zeling; Hao, Xiaolei; Li, Zhiguo (Utilitas Mathematica, 2018)
The book embedding of a graph G is setting the vertices in a line which called spine and the edges in a half plane so the edges embedded on the same page do not intersect. In this paper, the pagenumbers of Schrijver graph SG(2k + 2, k) and SG(2k +l,k) are obtained. © 2018 Utilitas Mathematica Publishing Inc. All rights reserved.